Empowering Qur’anic Learning Motivation through the Asset-Based Community Development Approach in the Tahfidz Program at TPA Al-Hikmah Centre Buluh Kasok - Fajri, Algusni (PT Agung Media Publisher, 2025)
This study investigates how the Asset-Based Community Development (ABCD) approach can be employed to enhance learning motivation in a tahfidz program at TPA Al-Hikmah Centre Buluh Kasok, a rural-based Qur’anic education center in Indonesia. The study adopts a qualitative case study design involving participatory observation, semi-structured interviews with tahfidz instructors, students, and parents, as well as document analysis. The research focuses on identifying community assets and examining their influence on students’ motivation to memorize the Qur’an. Data were analyzed using thematic coding within the framework of ABCD and motivational learning theories. Findings reveal that the ABCD approach significantly supports Qur’anic learning motivation through three pathways: (1) mobilization of local social and spiritual assets, including parental involvement and religious role models; (2) creation of a collaborative peer-based learning atmosphere; and (3) cultural and emotional reinforcement through communal rituals and recognition. Students who were embedded in these asset-driven learning environments demonstrated higher persistence, stronger memorization consistency, and more positive emotional engagement. These findings confirm that learning motivation in tahfidz education is influenced not merely by curriculum design or teacher-centered instruction but by the activation of communal and cultural capital. The study supports existing theories of intrinsic motivation and the social nature of learning, while also contributing to the limited literature on ABCD in Islamic educational contexts. Future research should expand this inquiry through longitudinal and comparative studies across diverse educational settings to better understand how community-driven strategies can be institutionalized in Qur’anic pedagogy.